TEOLOGI POLITIK DAN AGAMA “ADEM AYEM” - Eddy Kristiyanto (Litbang STFT Widya Sasana Malang, 2004)
Theology of politics intends to deconstruct individualistic practice of religious life. One of its bases is that the Messiah is the concrete expression of God’s concern to the autonomous world. Human being’s response to God’s concern is faith by which he embodies himself into institutional religion. But, what we call faith has often been personal (or, better, individualistic) affair. This article poses a thesis that such “adem ayem” relationship between religion and faith must be destroyed, and replaced by new relationship that religion and faith should be involved to and in the world, as it is threatened continuously by injustice, corruption, and violence. Perhaps this question is not unlikely: are we really religious while at the same time we do injustice, corruption and violence? We prevent that religion and faith are only formal to us as a mask. Theology of politics deconstructs such paradigm.